2021
DOI: 10.1158/1535-7163.mct-20-0287
|View full text |Cite
|
Sign up to set email alerts
|

HDP-101, an Anti-BCMA Antibody–Drug Conjugate, Safely Delivers Amanitin to Induce Cell Death in Proliferating and Resting Multiple Myeloma Cells

Abstract: Despite major treatment advances in recent years, patients with multiple myeloma inevitably relapse. The RNA polymerase II complex has been identified as a promising therapeutic target in both proliferating and dormant cancer cells. Alpha-amanitin, a toxin so far without clinical application due to high liver toxicity, specifically inhibits this complex. Here, we describe the development of HDP-101, an anti–B-cell maturation antigen (BCMA) antibody conjugated with an amanitin derivative. HDP-101 displayed high… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 43 publications
1
37
0
Order By: Relevance
“…This gene encodes an RNA polymerase II enzyme, which can be inhibited by amanitins [156,157]. This drug, conjugated with a targeted antibody against BCMA, has been tested in MM cell lines and mouse models with promising results [158]. Furthermore, the decrease of polymerase activity can be compensated by the overexpression of RBX1.…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…This gene encodes an RNA polymerase II enzyme, which can be inhibited by amanitins [156,157]. This drug, conjugated with a targeted antibody against BCMA, has been tested in MM cell lines and mouse models with promising results [158]. Furthermore, the decrease of polymerase activity can be compensated by the overexpression of RBX1.…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…Moreover, HDP-101 (an anti-B-cell maturation antigen (BCMA) antibody conjugated with an amanitin derivative) displayed high efficacy against both proliferating and resting myeloma cells in vitro, sparing BCMA-negative cells. These findings might provide a novel therapeutic approach to overcome drug resistance in this disease [56]. Recently, Gallo et al (2021) showed that α-amanitin-based small-molecule drug conjugates grafted onto an immunoglobulin Fc domain increased the pharmacokinetic properties and therapeutic efficacy over the small-molecule drug conjugates in a prostate cancer xenograft mouse model [57].…”
Section: Perspectivesmentioning
confidence: 99%
“…Soluble BCMA has been shown to interfere with anti-BCMA therapies by reducing the levels of active drug that reach multiple myeloma cells [ 155 ]. However, the H929 cell line, which expressed the highest relative amounts of cell surface and soluble BCMA, displayed the highest sensitivity to an investigational ADC [ 158 ]. This indicates that BCMA cell surface levels might have a greater impact on efficacy than the soluble BCMA concentration.…”
Section: Target Antigens For Approved Adcs and Their Endocytosis Characteristicsmentioning
confidence: 99%
“…However, the level of expression in normal B cells and multiple myeloma cells was not reported until recently. Utilizing a novel anti-BCMA ADC (HDP-101), Figueroa et al determined that the level of antibody-bound molecules against BCMA per cell ranged from 1171–8987 in the multiple myeloma cell lines H929, INA-6, U266, MM.1S-Luc, RPMI-8226, MM.1S, LP-1, OPM-2, SKMM.1, and L363 [ 158 ]. Importantly, this finding was in agreement with the number of bound antibodies per cell (1170–8987) measured in bone marrow plasma cells from patients with newly diagnosed or relapsed multiple myeloma.…”
Section: Target Antigens For Approved Adcs and Their Endocytosis Characteristicsmentioning
confidence: 99%